Invertebrates and the complexity of tropical ecosystems - Kitching, RL; Dahlsjö, CAL; Eggleton, P (Wiley, 2020)
It has been estimated that there are seven million terrestrial arthropod species on Earth consisting of 6.1 million species of insects, 1.5 million of which are beetles. Tropical forests hold a majority of these species, yet few such places have been adequately sampled for alpha diversity, and there remains even more uncertainty about beta diversity. From an ecological point of view, it is the functional role of organisms within ecosystems that is the particular focus. It has been customary to classify invertebrates within ecosystems in terms of their trophic roles, but it is also useful to consider their roles in networks. In broad terms, we can classify these networks on the grounds of their basal resources. Those based directly on the photosynthetic products of plants are so-called “green” food webs, and those based on dead and dying plant material are “brown” food webs. Here, we principally discuss the diversity and functional roles of the invertebrates in tropical terrestrial ecosystems. New sampling and analytical techniques, an expanded set of focal taxa, and an enhanced concern with interactions and processes hold the promise of a productive future for invertebrate studies in the tropics. These will not only add to general understanding of the dynamics of tropical ecosystems but will also provide powerful tools for monitoring and responding to environmental change.